2021
DOI: 10.1002/ardp.202100277
|View full text |Cite
|
Sign up to set email alerts
|

The anticancer activity of carbazole alkaloids

Abstract: Chemotherapy is the first choice for the majority of cancers, but severe side effects and drug resistance restrict the actual clinical efficacy. Carbazole alkaloids, mainly from the Rutaceae family, possess favorable donor ability, good planarity, rich photophysical properties, and excellent biocompatibility. Carbazole alkaloids could not only intercalate in DNA but could also inhibit telomerase and topoisomerase and regulate protein phosphorylation. Hence, carbazole alkaloids are useful in providing lead hits… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 71 publications
0
10
0
Order By: Relevance
“…Carbazole alkaloids have anti‐cancer activity because they intercalate in DNA and interfere with topoisomerase function. DNA replication stress is induced, which eventually leads to p53 activation (Caruso et al, 2016; Song et al, 2022). We surmise that this property of the carbazole core may have caused the enhanced cell death of T24 cells treated with a high concentration (20 μM) of DMPCA (Figure 3c).…”
Section: Discussionmentioning
confidence: 99%
“…Carbazole alkaloids have anti‐cancer activity because they intercalate in DNA and interfere with topoisomerase function. DNA replication stress is induced, which eventually leads to p53 activation (Caruso et al, 2016; Song et al, 2022). We surmise that this property of the carbazole core may have caused the enhanced cell death of T24 cells treated with a high concentration (20 μM) of DMPCA (Figure 3c).…”
Section: Discussionmentioning
confidence: 99%
“…It exhibits a number of biological activities 22,23 i.e. , anti-microbial, 24 anti-cancerous, 25 anti-inflammatory, 26 anti-viral, 27 neuroprotective 28 and anti-oxidative. 29 Among industrial applications, carbazole scaffold has found potential applications in fluorescent probes, 30 bioimaging devices, 31 organic semiconductors 32 and polymers 33,34 etc.…”
Section: Introductionmentioning
confidence: 99%
“…1). [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] In recent years, many research groups have remarkably found that carbazole derivative have divergent biological applications such as affinity to bind with estrogen receptors, 52 anti-tumor activity, [53][54][55][56] antiplasmodial, 57 antimalarial, 58 antibiotic, 59 antifungal, 60,61 etc. Besides their biological applications, they also have bioimaging properties, applications in developing OLEDs, [46][47][48][49] OFETs, 41 solardyes, 43 conducting polymers, 37 photovoltaic devices, 39 optoelectric properties, 38,40 and organic semiconductors.…”
Section: Introductionmentioning
confidence: 99%
“…35,36 Carbazole and its derivatives have attracted unique attention in synthetic organic chemistry and material sciences because of their numerous applications. 37–51 In recent years, various research groups have remarkably found that carbazole derivative have divergent biological applications such as affinity to bind with estrogen receptors, 52 anti-tumor activity, 53–56 antiplasmodial, 57 antimalarial, 58 antibiotic, 59 antifungal, 60,61 etc. Besides their biological applications, they also have bioimaging properties, applications in developing OLEDs, 46–49 OFETs, 41 solardyes, 43 conducting polymers, 37 photovoltaic devices, 39 optoelectric properties, 38,40 and organic semiconductors.…”
Section: Introductionmentioning
confidence: 99%